2013
DOI: 10.5667/tang.2013.0010
|View full text |Cite
|
Sign up to set email alerts
|

Genuine traditional Korean medicine, BaekJeol-Tang for the treatment of rheumatoid arthritis

Abstract: Inflammation in rheumatoid arthritis is characterized by immune cell infiltration and cytokine secretion. In particular, mast cells and their cytokines play an important role in the pathogenesis of rheumatoid arthritis. Korean medicine, BaekJeol-Tang (BT) was designed by traditional Korean medicine theory. We already reported therapeutic effect of BT in rheumatoid arthritis. Here, we report the specific underlying mechanism of BT in activated human mast cells, HMC-1 cells. In addition, we report for the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Štofilová et al () reported that the number of NF‐κB positive cells was significantly increased in intestinal inflammation. The expression of inflammatory cytokines in activated human mast cells is also positively correlated with enhanced NF‐κB expression (Han et al, ; Nam et al, ; Song et al, ) and increased NF‐κB activity has been identified in various inflammatory disorders (Choi, Kim, Ko, & Lee, ; Miagkov et al, ; Poynter, Irvin, & Janssen‐Heininger, ). Furthermore, many researchers have reported that targeted strategies to prevent NF‐κB activation, such as the use of natural products, small molecule inhibitors, and proteasome inhibitors, are effective in experimental allergic inflammatory models (Bao et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Štofilová et al () reported that the number of NF‐κB positive cells was significantly increased in intestinal inflammation. The expression of inflammatory cytokines in activated human mast cells is also positively correlated with enhanced NF‐κB expression (Han et al, ; Nam et al, ; Song et al, ) and increased NF‐κB activity has been identified in various inflammatory disorders (Choi, Kim, Ko, & Lee, ; Miagkov et al, ; Poynter, Irvin, & Janssen‐Heininger, ). Furthermore, many researchers have reported that targeted strategies to prevent NF‐κB activation, such as the use of natural products, small molecule inhibitors, and proteasome inhibitors, are effective in experimental allergic inflammatory models (Bao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the excessive phosphorylation of p38, ERK, and JNK were regarded as criteria to evaluate inflammatory activity. Diverse inhibitors targeting p38, ERK, and JNK pathways exhibit anti‐inflammatory effects through inhibition of the expression of inflammatory mediators (Han et al, ; Kang et al, ). The present study also showed that BS suppressed the PMACI‐induced phosphorylation of MAPKs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it seems that YouTube is aware of its position in the political landscape and is taking responsibility. For example, company leaders indicated that in the first quarter of 2019 alone, the company removed approximately 260,000 videos that violated its guidelines (Han et al, 2020). In this context, it is reasonable to ask whether YouTube and YouTube channels are entirely to blame for negative consequences such as polarization.…”
Section: Theoretical Background 21 Youtube As An Alternative Source O...mentioning
confidence: 99%
“…However, it seems that YouTube is aware of its position in the political landscape and is taking responsibility. For example, company leaders indicated that in the first quarter of 2019 alone, the company removed approximately 260,000 videos that violated its guidelines (Han et al. , 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%